Dual functional oyster shell-derived Ag/ZnO/CaCO3 nanocomposites with enhanced catalytic and antibacterial activities for water purification. Issue 70 (13th December 2019) - Chang, Lin; Feng, Yan; Wang, Bingqing; Huang, Xiaoyu; Yang, Da-Peng; Lu, Youguang
Abstract : Oyster shell was used as an efficient template for synthesis Ag/ZnO/CaCO3 nanocomposites, which showed the enhanced catalytic and antibacterial activities. Abstract : Transforming biological waste into high value-added materials has attracted extensive current research interest in the wastewater treatment field. In this study, oyster shell-derived CaCO3 was used as a solid support to construct efficient Ag/ZnO/CaCO3 via Cacumen platycladi extract. As compared to binary Ag/CaCO3 and ZnO/CaCO3, the as-obtained Ag/ZnO/CaCO3 exhibits excellent performance for the reduction of 4-nitrophenol (4-NP) with a reduction rate of 97.6% within 8 minutes. Furthermore, Ag/ZnO/CaCO3 exhibited superior antibacterial activity in inhibiting the growth of Escherichia coli ( E. coli ) and Staphylococcus aureus ( S. aureus ) with minimum inhibition concentrations (MICs) of 60 μg mL −1 and 30 μg mL −1, respectively. The observation of the superior activity for the reduction of 4-NP and antibacterial test of Ag/ZnO/CaCO3 can be attributed to the synergistic effect of Ag, ZnO and the oyster shell-derived CaCO3 . This study provides a strategy in developing highly efficient catalysts for the reduction of 4-NP and antibacterial agents based on the oyster shell-derived CaCO3 .